A Comparison of Tritium Dispersion Methodology for Accident Analysis in U.S. Department of Energy Complex Facilities. (3rd April 2017) - O'Kula, Kevin R.; Thoman, David C.; Guardiano, Selina K.; Hope, Eric P.
Abstract: A comparison of three United States (U.S.) Department of Energy (DOE) Standard DOE-STD-3009–2014 dispersion modeling protocol options has been performed assuming a ground-level release of tritium oxide source term. The options are characterized by differing sets of assumptions and inputs that allow incorporating greater user flexibility and realism into the modeling and subsequent analysis. The three options used to evaluate atmospheric dispersion include: (1) Use of U.S. Nuclear Regulatory Commission (NRC) Regulatory Guide 1.145; (2) Application of a DOE-approved toolbox code and application of conservative input parameters; and (3) Use of site-specific methods and parameters as defined in a site/facility specific DOE-approved modeling protocol. Option 1 dose results are the lowest of the three sets of results at close-in distances, but are the highest for distances beyond approximately 3, 000 m, reflecting the distance-dependent NRC plume meander model. Option 1 doses also reflect a lower minimum wind speed and consideration of G stability. Option 3 dose results are consistently lower than the Option 2 results by a factor of 2.2 reflecting the higher vertical dispersion values calculated from the crediting site-specific surface roughness. Option 2 and 3 results are obtained with DOE Central Registry computer software reflect default parameters in Option 2, and more site-specific input with Option 3. An averaging time of two hours leads to dose results that are lower than those obtained with an averaging time of three minutes by a factor of 2.5 due to the higher crosswind dispersion parameter values. This effect is due to the larger crosswind dimension of the plume with increasing averaging time using the Gifford meander model. A sensitivity case study indicates appreciable differences are observed between results obtained with the NRC Regulatory Guide 1.145 temperature difference (ΔT) method and those with U.S. Environmental Protection Agency (EPA) EPA-454/R-99–005 methodology for stability class categorization. A second sensitivity case suggests that crediting deposition, hold-up or other retention of tritium may be difficult to defend from a regulatory perspective, recognizing region of transport characteristics and accounting for reemission phenomenon. In terms of recommending one of the three options for modeling tritium releases in Documented Safety Analysis (DSA) applications, the Option 2 approach (Application of a DOE-approved toolbox code and conservative input parameters – without crediting tritium deposition) is the simplest model for source to receptor distances of 500 m or greater. Option 3 requires additional resource commitment and DOE authority approval, but may provide regulatory relief for certain accident scenarios. These recommendations apply to deterministic DSA dispersion analysis but are not extended to best estimate, realistic analyses such as those supporting probabilistic safety analyses.